Arthropods Under Pressure: Stress Responses and Immunity at the Pathogen-Vector Interface - Rosche, Kristin L.; Sidak-Loftis, Lindsay C.; Hurtado, Joanna; Fisk, Elizabeth A.; Shaw, Dana K. (Frontiers in Immunology, 2021)
Understanding what influences the ability of some arthropods to harbor and transmit pathogens may be key for controlling the spread of vector-borne diseases. Arthropod immunity has a central role in dictating vector competence for pathogen acquisition and transmission. Microbial infection elicits immune responses and imparts stress on the host by causing physical damage and nutrient deprivation, which triggers evolutionarily conserved stress response pathways aimed at restoring cellular homeostasis. Recent studies increasingly recognize that eukaryotic stress responses and innate immunity are closely intertwined. Herein, we describe two well-characterized and evolutionarily conserved mechanisms, the Unfolded Protein Response and the Integrated Stress Response, and examine evidence that these stress responses impact immune signaling. We then describe how multiple pathogens, including vector-borne microbes, interface with stress responses in mammals. Owing to the well-conserved nature of the UPR and ISR, we speculate that similar mechanisms may be occurring in arthropod vectors and ultimately impacting vector competence. We conclude this Perspective by positing that novel insights into vector competence will emerge when considering that stress-signaling pathways may be influencing the arthropod immune network.